If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -16 = 3h + -6 Reorder the terms: -16 + -2x = 3h + -6 Reorder the terms: -16 + -2x = -6 + 3h Solving -16 + -2x = -6 + 3h Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + -2x = -6 + 16 + 3h Combine like terms: -16 + 16 = 0 0 + -2x = -6 + 16 + 3h -2x = -6 + 16 + 3h Combine like terms: -6 + 16 = 10 -2x = 10 + 3h Divide each side by '-2'. x = -5 + -1.5h Simplifying x = -5 + -1.5h
| (8-3i)(2+7i)= | | -2p-1=5p-8 | | x^2+4=9x | | 6-(-30)= | | 30-18=6x | | 4a+10=10 | | y-8=0.14(x+9) | | =3(x-3.8)(x+1.2) | | 2(x-1)=5x-14 | | 187=-11x+55 | | 10-2h=3 | | 5(3c+2)=4(5c-10) | | 2cotx+sec^2x=0 | | 6(7-2p)=-38-2p | | -9.01-(-8.57)= | | -6x-10=8+5(8-7x) | | -84=7k | | 4(3c-6)=36 | | 13x+40=180 | | 30+150g=500 | | 5(2c-6)=40 | | -z+6z-10=15 | | 26=5x-4(4x+10) | | f+5=-7 | | 7(7+2r)=23+r | | 1/2(2+y)+y=6 | | -4x+0.4=14 | | 500+150g=30 | | (-9x^3)(x^8+x)= | | 7=-3+r | | 8+y-6x=7 | | -3v-27=6(v+6) |